Application of zirconium sulfate oxide solid superacid and nickel carbon catalyst in concerted catalysis of lignite model compound for hydrodeoxygenation
Through the coordinated catalysis of zirconium oxide solid super acid and nickel carbon catalyst, the problem of catalyst interaction restricting the reaction conversion rate is solved, and efficient hydrodeoxygenation of lignite model compounds under mild conditions, especially diphenyl ether 100 The % conversion rate and high selectivity of cyclohexane simplify catalyst preparation and improve reaction efficiency.
Patent Information
- Application Number
- CN202411345015.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-25
AI Technical Summary
In the hydrodeoxygenation reaction of existing catalysts, there is a problem that the interaction between active metal and support restricts the reaction conversion rate, and conventional bifunctional catalysts are difficult to effectively crack the C-O bridge bonds in lignite under mild conditions.
The coordinated catalysis of zirconium oxide solid superacid and nickel carbon catalyst is adopted to prepare the catalyst through physical mixing, combining precipitation and impregnation methods, so as to achieve efficient hydrodeoxygenation of lignite model compounds under mild conditions.
The 100% conversion of lignite model compounds and the high selectivity of cyclohexane were achieved under conditions of 140°C, 1MPa H2 and 2h, which simplified the catalyst preparation method, improved the reaction efficiency, and reduced the risk of equipment corrosion.
Smart Images

Figure CN119215937A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to application of sulfated zirconium oxide solid superacid and nickel-carbon catalyst in synergistic catalysis of hydrodeoxygenation of lignite model compounds. Background Art
[0002] The organic matter in lignite is mainly composed of aromatic structural units connected by bridge bonds, and among the bridge bonds connecting aromatic structural units, CO bridge bonds are the main connection mode, especially CO ether bonds. Due to the high oxygen content of lignite, the direct use of hydrocracking oil is limited by some disadvantages, such as low energy density, corrosiveness and high viscosity, so a deoxygenation upgrading process is required, namely the so-called hydrodeoxygenation (HDO). The conversion of coal and model compounds generally requires high temperature and high pressure reaction conditions, and it is crucial to select a catalyst that can achieve its efficient conversion under mild conditions.
[0003] Solid superacid catalysts are environmentally friendly catalysts with the advantages of super acidity, stability, reusability, no corrosion to equipment, and no pollution to the environment. Among them, metal oxide solid superacids can enhance the efficient adsorption and dissociation of hydrogen molecules under mild conditions in hydrogenation catalytic reactions due to their stronger acid sites, and can enhance the adsorption of coal macromolecules on the catalyst, and ultimately promote the directional cracking of the CO bridge bond connecting the aromatic rings in coal organic matter. In conventional bifunctional catalysts, the interaction between the active metal and the carrier restricts the conversion rate of the reaction, and the physical mixing of two catalysts with different functions is a promising and simple solution that can avoid the problems caused by the interaction of the two catalysts while maintaining their respective functions. Summary of the invention
[0004] The purpose of the present invention is to provide an application of sulfated zirconium oxide solid superacid and nickel-carbon catalyst to synergistically catalyze the hydrodeoxygenation of lignite model compounds, thereby avoiding problems caused by the interaction of the two catalysts and improving the conversion rate of the reaction.
[0005] To achieve the above object, the technical solution adopted by the present invention is as follows: application of sulfated zirconium oxide solid superacid and nickel-carbon catalyst to synergistically catalyze the hydrodeoxygenation of lignite model compounds, and the specific steps include:
[0006] A substrate lignite model compound, a catalyst and n-hexane are placed in a reactor, wherein the catalyst is composed of a sulfated zirconium oxide solid superacid catalyst and a nickel-carbon catalyst in a mass ratio of 1 to 5:5; after sealing, residual air is removed by introducing hydrogen; subsequently, the reactor is pressurized to a desired pressure (0.1 to 2 MPa) with hydrogen at room temperature, and then the temperature is raised to the required reaction temperature of 140 to 180° C., and the reaction is stirred for 2 to 4 hours; after the experiment is completed, the reaction system is naturally cooled to room temperature and the pressure is released; the reaction mixture is filtered to remove the catalyst, and the organic phase is obtained by gas chromatography-mass spectrometry and gas phase analysis.
[0007] As a preferred embodiment of the present invention, the sulfated zirconium oxide solid superacid catalyst is prepared by a precipitation method, and the specific steps include: preparing a zirconium oxychloride aqueous solution, adjusting the pH value of the solution to 9-10 under stirring conditions, stirring and reacting for 24 hours, centrifuging and washing with water to neutrality, and vacuum drying overnight, grinding and adding 0.5 mol / L sulfuric acid, stirring and reacting for 6 hours, and then filtering and drying; grinding the dried solid into powder and transferring it to a tube furnace, calcining it at 500-600°C and in an inert atmosphere for 3 hours to obtain a solid superacid 0.5-SO4 2- / ZrO2.
[0008] As a preferred embodiment of the present invention, the active component in the nickel-carbon catalyst is metallic nickel, the carrier is activated carbon, and the nickel loading is 10%.
[0009] As a more preferred embodiment of the present invention, the nickel-carbon catalyst is prepared by an impregnation method, and the specific steps include: adding an activated carbon carrier to an aqueous nickel nitrate solution, ultrasonicating for 15 to 30 minutes, and then vacuum impregnating the mixture at room temperature for 24 hours, and drying after the impregnation is completed; thereafter, the solid sample is first calcined at 450°C for 2 hours in an inert atmosphere, and then reduced at 450°C for 2 hours in a H2 atmosphere to obtain a catalyst 10% Ni / AC.
[0010] As a preferred embodiment of the present invention, the lignite model compound is one of diphenyl ether, benzyl phenyl ether, phenoxyethylbenzene, p-xylyl ether, 4-phenoxyphenol and dibenzyl ether.
[0011] As a preferred embodiment of the present invention, the stirring speed is 800-900 rpm.
[0012] As a preferred embodiment of the present invention, the mass ratio of the amount of the catalyst to the substrate is 1:1.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] 1. The present invention uses SO4 2- / ZrO2 and 10% Ni / AC were used as catalysts, and under mild conditions of 140°C, 1MPa H2 and 2h, a 100% conversion rate of the lignite model compound diphenyl ether and a high selectivity of 100% for cyclohexane were achieved. The catalyst preparation method is simple, and only physical mixing is required to obtain high hydrodeoxygenation activity.
[0015] 2. The present invention uses SO4 2- / ZrO2 and 10% Ni / AC are used as catalysts, and under the reaction conditions of 140-180°C, 2-4h and 1MPa H2, the CO ether bond cleavage of different model compounds of lignite including diphenyl ether, benzyl phenyl ether, phenoxyethylbenzene, p-xylyl ether, 4-phenoxyphenol and dibenzyl ether can be achieved, and most of the products are oxygen-free compounds. The present invention is of great significance for achieving deoxygenation and upgrading of coal pyrolysis oil. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 are the XRD spectra of different catalysts.
[0017] Figure 2 These are the NH3-TPD diagrams of different solid super acids.
[0018] Figure 3 are the XPS patterns of different catalysts.
[0019] Figure 4 TEM and particle size distribution diagrams of different catalysts.
[0020] Figure 5 are SEM images of different catalysts.
[0021] Figure 6 The effect of the concentration of sulfuric acid used to synthesize solid superacid on the conversion of diphenyl ether.
[0022] Figure 7 It is the effect of reaction temperature on the conversion of diphenyl ether.
[0023] Figure 8 It is the effect of reaction pressure on the conversion of diphenyl ether. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0025] Embodiment 1:
[0026] (1) Preparation of SO4 by precipitation method 2- / ZrO2:
[0027] All solid superacid catalysts are prepared by precipitation method. In a typical process, 2g ZrOCl2·8H2O is weighed, dissolved in deionized water and sonicated at room temperature for 5min. Ammonia water is slowly added dropwise under stirring to adjust the pH value of the solution to 9-10. After stirring for 24h, the solution is centrifuged and washed with deionized water until neutral. The obtained solid is vacuum dried at 70°C overnight, ground and 15mL sulfuric acid is added, stirred for 6h, then filtered and dried. The dried solid is ground into powder and calcined in a tube furnace at 550°C and argon environment for 3h to obtain solid superacid n-SO4 2- / ZrO2, abbreviated as n-SZ (n=0, 0.25, 0.5, 0.75 and 1, representing the concentration of sulfuric acid, the unit is mol / L).
[0028] (2) Preparation of 10% Ni / AC by impregnation method:
[0029] The 10% Ni / AC catalyst was prepared by impregnation. 5 mL of deionized water was added to 0.5505 g of Ni(NO3)2·6H2O and stirred at room temperature for 5 min, then 1 g of activated carbon carrier was added and ultrasonicated for 15 min, and the mixture was impregnated in vacuum at room temperature for 24 h. Then it was dried at 110 °C for 12 h. After that, the solid sample was first calcined at 450 °C for 2 h in a nitrogen atmosphere, and then reduced at 450 °C for 2 h in a H2 atmosphere. The catalyst 10% Ni / AC was obtained.
[0030] 10% Ni / 0.5-SZ and 10% Ni-0.5-SZ / AC catalysts were prepared by the same method using 0.5-SZ and 0.5-SZ / AC as carriers for comparative experiments.
[0031] (3) Characterization of catalyst:
[0032] from Figure 1 It can be seen from the XRD patterns that the Ni-based catalyst supported on activated carbon and the Ni-based catalyst supported on solid superacid have observed diffraction peaks of Ni(111) and Ni(200) crystal planes at 44.5° and 51.8°. For the solid superacid supported nickel catalyst and the n-SZ samples treated with sulfuric acid at different concentrations, obvious diffraction peaks were observed near 2θ=30.3°, 35.3°, 50.4° and 60.2°, corresponding to the (011), (110), (112) and (121) crystal planes of tetragonal zirconia, respectively. Among them, the characteristic peaks of tetragonal zirconia of 0.5-SZ are particularly prominent. In addition to the above characteristic peaks, 0-SZ without sulfuric acid treatment also shows obvious monoclinic phase diffraction peaks at 2θ=24.4°, 28.2°, 31.5° and 34.2°. The n-SZ catalysts treated with sulfuric acid all showed a zirconia tetragonal crystal structure, which may be the reason why this solid superacid catalyst has excellent catalytic performance.
[0033] The acidity of different solid superacids treated with different sulfuric acids was determined by NH3-TPD characterization method. Generally speaking, the acidity distribution in the NH3-TPD curve can be divided into four different regions, and the peaks at these four different temperatures represent weak acid sites (T < 300 °C), medium strong acid sites (300 °C < T < 450 °C), strong acid sites (450 °C < T < 600 °C), and super strong acid sites (T > 600 °C), respectively. As Figure 2 shown, 0-SZ without sulfuric acid treatment has almost no acidity, while desorption peaks appear above 600 °C for n-SZ prepared by different sulfuric acid treatments, indicating that the prepared catalysts have solid superacidic properties. It can be seen that the desorption temperature of the solid superacid gradually increases with the increase of sulfuric acid concentration, indicating that the higher the sulfuric acid concentration, the stronger the acidity of the obtained solid superacid. However, the peak area of 0.5-SZ is the largest, that is, the acid amount is the largest. The appropriate acidity and relatively high acid amount may be one of the reasons for the best activity of this catalyst.
[0034] The prepared catalysts were detected by XPS to observe the actual chemical valence state of the active metal Ni in the catalysts. As Figure 3 shown, for the 10% Ni / AC catalyst, the content of metal Ni dispersed on the surface of AC 0 is the highest, reaching 30.8%; for the 10% Ni / 0.5-SZ catalyst, the content of metal Ni 0 on the surface of 0.5-SZ is 9.8%; for the 10% Ni-0.5-SZ / AC catalyst, the content of metal Ni 0 on the surface of 0.5-SZ / AC is the lowest, only 8.4%. Generally speaking, the higher the content of metal Ni 0 in the catalyst, the more favorable it is for hydroconversion, which helps the activation and dissociation of hydrogen to generate active hydrogen. Therefore, the 10% Ni / AC catalyst has relatively higher activity.
[0035] The particle size of metal nanoparticles is an important factor affecting the hydrogenation reaction of hydrogenation catalysts. The smaller the particle size of metal particles in the catalyst, the better its dispersion, so there are relatively more active sites, which plays a key role in the adsorption, activation and dissociation of H2, as well as the adsorption and reaction of reactants. As Figure 4As shown in the figure, for the 10% Ni / AC catalyst, the average particle size of the metal Ni dispersed on the AC surface is about 7.85nm; while for the 10% Ni / 0.5-SZ catalyst, the metal Ni on the 0.5-SZ surface is severely agglomerated, with an average particle size of up to 21.57nm. The high degree of metal agglomeration may be an important reason for its extremely low catalytic activity; however, for the 10% Ni-0.5-SZ / AC catalyst, although the average particle size of the metal Ni on the 0.5-SZ / AC surface is smaller, only 6.44nm, the metal loading will lead to severe coverage of the catalyst active sites and acid sites, and the active metal Ni in the catalyst 0 The content of is the lowest, therefore, the catalyst activity does not increase but decreases.
[0036] As shown in Table 1, the prepared 10% Ni / AC catalyst has abundant microporous and mesoporous structures, a large specific surface area, which is conducive to the dispersion of active metals, and a small pore size. For the prepared n-SZ catalyst, there is a small specific surface area, and the specific surface area is mainly mesoporous structure with a large pore size. The treatment of sulfuric acid will help to form more mesoporous structures and reduce the pore size.
[0037] Table 1 Pore structure information of different catalysts
[0038]
[0039] S BET : Total pore specific surface area; S micro : Micropore specific surface area; S meso : mesopore specific surface area; V total : Total pore volume; V micro : Micropore volume; V meso : mesopore volume; D ave : Average pore diameter.
[0040] a : Determined by multi-point BET method; b : Determined by t-plot method; c : Calculated based on nitrogen absorption at a relative pressure P / P0 of 0.99; d :Use the subtraction method.
[0041] SEM characterization was used to observe the morphological features of AC, 10% Ni / AC and 0.5-SZ samples. Figure 5 As shown in the figure, there are abundant pore structures on the surface of AC and 10% Ni / AC, and the metal Ni is evenly dispersed on the surface of AC. The surface of 0.5-SZ sample is relatively rough, and there are also certain pore structures.
[0042] Example 2: Application of the synthesized catalyst to the hydrogenation of diphenyl ether
[0043] Take the hydrodeoxygenation reaction of diphenyl ether as an example:
[0044] All hydrodeoxygenation reactions were carried out in a 100 mL stainless steel autoclave. In a typical experiment, the substrate diphenyl ether (100 mg), catalyst and n-hexane (20 mL) were placed in the reactor. After sealing, the residual air was removed by passing hydrogen three times. Subsequently, the reactor was pressurized to the desired pressure (1 MPa) with hydrogen at room temperature. The temperature was then raised to the desired reaction temperature (140 ° C) and maintained for a certain time (60 min) at a vigorous stirring speed of 800 rpm. After the experiment, the reaction system was naturally cooled to room temperature and the pressure was released. The reaction mixture was filtered to remove the catalyst, and the organic phase obtained was analyzed by gas chromatography-mass spectrometry (GC-MS) and gas phase (GC), wherein the main products of diphenyl ether cracking were benzene (Benzene), cyclohexane (Cyclohexane), cyclohexanol (Cyclohexanol), oxydicyclohexane (OCE) and cyclohexyl phenyl ether (CPE).
[0045] Table 2 Comparison of diphenyl ether hydrodeoxygenation reactions catalyzed by different catalysts
[0046]
[0047] Reaction conditions: 100 mg diphenyl ether, 20 mL n-hexane, 140 °C, 1 h, 1 MPaH2, M = AC, n-SZ (n = 0, 0.25, 0.5, 0.75 and 1); a 50 mg catalyst; b 100 mg catalyst; c 50 mg 10% Ni / AC and 50 mg solid superacid.
[0048] The catalytic activity of the catalyst was evaluated by catalyzing the hydrodeoxygenation of diphenyl ether under mild conditions (140°C, 1MPa H2). As can be seen from Table 2, diphenyl ether cannot be converted without a catalyst and using only AC and n-SZ. Under the same reaction conditions, the conversion rate of diphenyl ether on 10% Ni / AC is higher than that on 10% Ni / 0.5-SZ and 10% Ni-0.5-SZ / AC. The main reason why 10% Ni / 0.5-SZ has almost no catalytic activity is that the metal nickel is severely agglomerated on the 0.5-SZ support and Ni 0The content is low. When solid acid is added to the reaction system to jointly catalyze the reaction of diphenyl ether with 10% Ni / AC, the conversion rate of diphenyl ether is significantly improved. It is worth noting that after adding HZSM-5 and 0.5-SZ, the selectivity of cyclohexane in the product is significantly improved. Compared with HZSM-5, 0.5-SZ has better catalytic activity. Similarly, when 10% Ni / AC and 0.5-SZ synergistically catalyze the hydrodeoxygenation of diphenyl ether, the conversion rate of diphenyl ether is significantly higher than that of a single 10% Ni / AC catalyst. Even if the dosage of 10% Ni / AC is increased to 100 mg, the conversion rate of diphenyl ether is significantly lower than that in the presence of solid super acid. It can be seen that the addition of solid superacid can promote the hydrogenation conversion of diphenyl ether, so that it can produce more cyclohexane through hydrogenation deoxygenation reaction.
[0049] 10% Ni / AC and 0.5-SZ showed the best activity in the hydrodeoxygenation of diphenyl ether. Figure 6 The effect of adding solid super acid treated with different concentrations of sulfuric acid to the catalytic system on the conversion of diphenyl ether is shown. When 0-SZ, which has not been treated with sulfuric acid, is added, the conversion of diphenyl ether and the product distribution are similar to those when only 10% Ni / AC is added. When 0.25-SZ is added, the conversion of diphenyl ether and the selectivity for cyclohexane increase significantly and reach a maximum value when the sulfuric acid concentration is 0.5 mol / L, which is the optimal sulfuric acid concentration. When the sulfuric acid concentration is too high, the conversion of diphenyl ether and the selectivity for cyclohexane decrease slightly. Therefore, subsequent experiments will use 0.5-SZ and 10% Ni / AC as catalysts in n-hexane.
[0050] like Figure 7 As shown in the figure, under 1MPa H2 conditions, with n-hexane as the solvent, as the reaction temperature increases from 100°C to 140°C, the conversion of diphenyl ether and the selectivity of cyclohexane gradually increase, both reaching 100% at 140°C, while the selectivity of benzene gradually decreases to 0 as the temperature increases. In the whole process, the selectivity of oxydicyclohexane is very low, and at 140°C, no oxydicyclohexane is detected in the product.
[0051] like Figure 8 As shown in the figure, the effect of hydrogen pressure on diphenyl ether conversion and cyclohexane selectivity was investigated. Low hydrogen pressure (0.1MPa) resulted in low diphenyl ether conversion and cyclohexane selectivity. With the increase of hydrogen pressure, the diphenyl ether conversion and cyclohexane selectivity increased rapidly, reaching a maximum value of 100% at 1MPa, and then remained unchanged. It can be seen that with the increase of H2 pressure, the selectivity of benzene gradually decreased. Therefore, the optimal H2 pressure determined in this study is 1MPa, at which diphenyl ether can be completely converted into cyclohexane.
[0052] Example 3: Application of the synthesized catalyst to hydrogenation of different lignite model compounds
[0053] Using 10% Ni / AC and 0.5-SZ as catalysts, the hydrogenation conversion of different lignite model compounds was investigated. As shown in Table 3, diphenyl ether, benzyl phenyl ether, phenoxyethylbenzene, p-xylyl ether, 4-phenoxyphenol and dibenzyl ether all have catalytic effects. Under relatively mild conditions (<180°C and 1MPa H2), they can effectively crack the CO bond with a conversion rate of 100%. The yield of oxygen-containing products is low. The catalyst can effectively catalyze the hydrodeoxygenation reaction of lignite model compounds to generate oxygen-free compounds.
[0054] Table 3 Hydrogenation conversion results of different lignite model compounds on 10% Ni / AC and 0.5-SZ
[0055]
[0056] a Reaction conditions: 100 mg reactant, 50 mg 10% Ni / AC and 50 mg 0.5-SZ, 20 mL n-hexane, 1 MPa H2.
[0057] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. Application of sulfated zirconium oxide solid superacid and nickel-carbon catalyst to synergistically catalyze the hydrodeoxygenation of lignite model compounds, characterized in that: The specific steps include: A substrate lignite model compound, a catalyst and n-hexane are placed in a reactor, wherein the catalyst is composed of a sulfated zirconium oxide solid superacid catalyst and a nickel-carbon catalyst in a mass ratio of 1 to 5:5; after sealing, residual air is removed by introducing hydrogen; subsequently, the reactor is pressurized to 0.1 to 2 MPa with hydrogen at room temperature, and then the temperature is raised to the required reaction temperature of 140 to 180° C., and the reaction is stirred for 2 to 4 hours; after the experiment is completed, the reaction system is naturally cooled to room temperature and the pressure is released; the reaction mixture is filtered to remove the catalyst, and the organic phase is obtained by gas chromatography-mass spectrometry and gas phase analysis.
2. The use according to claim 1, characterized in that: The catalyst is composed of a sulfated zirconium oxide solid superacid catalyst and a nickel-carbon catalyst in a mass ratio of 1:
1.
3. The use according to claim 1 or 2, characterized in that: The solid superacid catalyst of zirconium sulfate oxide is prepared by a precipitation method, and the specific steps include: preparing a zirconium dichloride aqueous solution, adjusting the pH value of the solution to 9-10 under stirring conditions, stirring and reacting for 24 hours, centrifuging and washing with water to neutrality, and vacuum drying overnight, grinding and adding 0.5 mol / L sulfuric acid, stirring and reacting for 6 hours, and then filtering and drying; grinding the dried solid into powder and transferring it to a tube furnace, calcining it at 500-600° C. and in an inert atmosphere for 3 hours to obtain a solid superacid 0.5-SO4 2- / ZrO2.
4. The use according to claim 1 or 2, characterized in that: The active component of the nickel-carbon catalyst is metal nickel, the carrier is activated carbon, and the nickel loading is 10%.
5. The use according to claim 4, characterized in that: The nickel-carbon catalyst is prepared by an impregnation method, and the specific steps include: adding an activated carbon carrier to a nickel nitrate aqueous solution, ultrasonicating for 15 to 30 minutes, and then vacuum impregnating the mixture at room temperature for 24 hours, and drying after the impregnation is completed; thereafter, the solid sample is first calcined at 450°C for 2 hours in an inert atmosphere, and then reduced at 450°C for 2 hours in a H2 atmosphere to obtain a catalyst 10% Ni / AC.
6. The use according to claim 1 or 2, characterized in that: The lignite model compound is one of diphenyl ether, benzyl phenyl ether, phenoxyethylbenzene, p-xylyl ether, 4-phenoxyphenol and dibenzyl ether.
7. The use according to claim 1 or 2, characterized in that: The stirring speed is 800-900 rpm.
8. The use according to claim 1 or 2, characterized in that: The mass ratio of the amount of the catalyst to the substrate is 1:1.
Citation Information
Patent Citations
High-activity Ru / S-HZSM-5 catalyst as well as preparation method and application thereof
CN113181955A
Preparation of activated carbon loaded solid superacid catalyst and application of activated carbon loaded solid superacid catalyst in hydrogenolysis of aryl ether C-O bond
CN116747879A
Preparation method and application of high-activity HZSM-5 supported solid superacid catalyst
CN116786155A
Cited By
Hydrocracking catalyst for preparing aviation fuel as well as preparation method and application of hydrocracking catalyst
CN119633850A
A hydrocracking catalyst for producing aviation fuel, its preparation method and application
CN119633850B